Conocimiento de la comunidad del sector salud en la UAN sobre la terapia asistida con animales (2020)
Animal Assisted Therapy (TAA) consists of the use of an animal in a series of therapeutic interventions, to improve the cognitive, affective, and/or social functions of the patients in which it is implemented. To date, to our knowledge, there have been no research studies related to TAA in Colombia. The objective of the present study was to assess the level of knowledge that the health sector at the Antonio Nariño University (UAN) has about TAA. For this, a face-to-face survey was carried out with a total of 13 closed questions with multiple answers to students and teachers who, linked to the careers of psychology, Psychosocial Therapies, and Medicine at the UAN headquarters inBogotá. The results obtained show that, of the surveyed population, (56.2%) knew about animal-assisted therapy, (51.7%) of respondents would implement this type of therapy with their patients, while one (5.3 %) would not implement it. Regarding the use of animals as therapeutic support (73.7%) agree with the help provided by animals (horse, dog, among others) in certain patients, while(18.4%) is not in agreement and finally (7.9%) are indifferent as to they apply or not animal aid is applied. In conclusion, although a high percentage of the surveyed population knows and would use the TAA, we consider that the knowledge, use, and practice of animal-assisted therapy should be promoted in the country in such a way that it becomes additional support for people in need nationwide. Likewise, we recommend carrying out a similar study in the veterinary union to stimulate knowledge of the subject within agricultural professionals, providing professionals who can guarantee the integrity of the patient and of the animals used in the application of the therapy, reducing any the risk that can show up.